A proposed Conception to Develop the Professional Competencies of the Shadow Teacher according to the Techniques of The TEACCH program - Aya Elrashidy (International Journal of Instructional Technology and Educational Studies)
The aim of the current research is to develop a vision that contributes to developing the professional competence of the shadow teacher, given the importance of the research topic, which is the importance of the shadow teacher in the current educational integration process, as approved by Ministerial Resolution No. (42) Of 2015 and despite its importance, its preparation and development was neglected. It is necessary for him to carry out his tasks of treating and raising children with special needs and from here came the research problem, which is represented in: Lack of interest in preparing the shadow teacher appropriate preparation in parallel with the tasks assigned to him, The lack of programs to develop the professional aspects of the shadow teacher, The lack of a renewed form of the professional competencies that must be available in the shadow teacher.The results of the research explain the professional competencies of the shadow teacher and how to develop them through the use of therapeutic and educational techniques for one of the most famous and most effective treatment programs, which is the TEACCH0 program